l-Carnitine for the Treatment of a Calcium Channel Blocker and Metformin Poisoning - St-Onge, Maude (Springer US, 2013)
INTRODUCTION: The object of the current communication is to discuss the theory and the evidence for the use of l-carnitine in calcium channel blocker and metformin poisonings. CASE REPORT: A 68-year-old male known for hypertension and type II diabetes was admitted to the critical care unit of a community hospital following an overdose of amlodipine and metformin. The patient was intubated, ventilated, and hemodynamically supported with vasopressors. Despite calcium, glucagon, high-dose insulin (HDI), and lipid emulsion for calcium channel blocker and bicarbonate for metabolic acidosis, the patient remained hemodynamically unstable. The patient was considered too unstable to initiate continuous renal replacement therapy; and without access to extracorporeal life support, the administration of l-carnitine was administered as a last resort. One hour after l-carnitine, the norepinephrine requirements started to decrease, the patient began to improve and was subsequently extubated successfully without apparent sequelae in less than 4 days. DISCUSSION: l-Carnitine combined with HDI may have helped with the calcium channel blocker (CCB) poisoning by decreasing insulin resistance, promoting intracellular glucose transport, facilitating the metabolism of free fatty acids, and increasing calcium channel sensitivity. It may have also stimulated oxidative utilization of glucose instead of converting pyruvate into lactate and contributed to decrease lactate production with metformin poisoning.